L’autore (quasi)-personaggio e altre identità mutevoli nella prosa romena postmodernista (ENTHYMEMA, 2020)
In this paper I shall present some of the defining features of characterization in Romanian literature during the 80s and 90s of the 20th century, as well as the beginning of the 21st century. Namely, the first-person protagonist of a novel, above all within the literary paradigm created by Romanian Postmodernism, which has shown itself to be the most innovative, interesting and fruitful prose model in recent decades in Romania. In an overview of Romanian literature at the end of the 20th century, dominated by an autobiographical-driven style of fiction on the part of the author, an analysis of homo fictus also presupposes the exploration of other ideas connected with the narrative artefact, along with the relationship established between reality and fiction. Some of these links will be indicated in the texts analysed in this paper, first in the prose of Mircea Cărtărescu and, in a more synthetic approach, in some novels and short stories by Matei Vişniec and Ştefan Agopian. I have focused on the character-author, or rather, the author-character; but it will be seen that this pairing is imbued with polysemous significance and nuances that, to the reader’s eyes, blur the framework of this duo of critical-literary categories, making them hazier and more difficult to grasp.